RISK ESTIMATION OF CARDIOVASCULAR DISEASES AMONG INDIGENOUS ADULTS OF THE KRENAK ETHNICITY, MINAS GERAIS, BRAZIL. - Chagas, Cristiane Alvarenga; Ribeiro de Sá, Ricardo Américo; de Castro, Teresa Gontijo; da Silva Miranda, Aline Elizabeth; Leite, Maurício Soares; Pimenta, Adriano Marçal (Ciencia, Cuidado e Saude, 2023)
Objective: to estimate the risk of cardiovascular diseases in indigenous Krenak through the Framingham Cardiovascular Risk Score. Methodology: cross-sectional epidemiological study conducted with indigenous people aged 30 to 74 years, in Indigenous Land located in the eastern region of Minas Gerais, Brazil. The data collected were: weight and height to calculate BMI, measurement of blood pressure and casual capillary blood glucose, sex, age and smoking. The cardiovascular risk estimated at 10 years was calculated from the Framingham Score algorithm. In addition, normal cardiovascular risk, optimal cardiovascular risk and cardiovascular age were calculated. The sample was characterized with the presentation of absolute and relative frequencies of the variables that make up the cardiovascular risk score of Framingham, stratified by sex. Results: it was observed that cardiovascular risk at 10 years among the Krenak indigenous was higher than normal risk, as well as cardiovascular age was higher than chronological age, although most of the sample had a low cardiovascular risk at 10 years, no statistical difference between the sexes. Conclusion: despite the predominance of low cardiovascular risk in 10 years among the Krenak indigenous, the result of cardiovascular age above chronological age can cause morbidity and mortality from cardiovascular diseases over time in this population.